The Improvement reasoning ability of students to mathematic and logic through colour chip worksheet in the basic education unit in Tanjung Morawa - Nasution, Putri Khairiah; Syahmarani , Aghni; Yanti , Maulida (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Learning media is tools for teaching and learning process. Related to the use of instructional media as a component that can help teachers and students in the learning process. In learning mathematics at SDIT Deli Insani, there is still lack of learning media as a component in the learning process. The selection of the most appropriate media that must be considered to achieve the expected goals is to stimulate the ability to choose, increase communication power, stimulate independence, encourage motivation, and increase student creativity. The worksheet is a piece of learning media as well as an innovative game that can be carried around, the exam material is in accordance with the K-13 curriculum for elementary school students grade 1 to 4. By taking a sample of students grade 3 and 4 consist of 30 students per class, done a pre-test about material of mathematics, then explained the use of color chip worksheets. Next, learned the material using a worksheet of color chips. And finally, a post test was conducted to measure up which students could absorb the material. The evaluation, carried out about 2 months after the training, the teachers and students have independently used a worksheet of color chips and the students' abilities significantly improved.